Practices of breeding aedes mosquitoes and factors related with it amongs residents of Kampung Padang Jawa, Petaling Selangor, 1995 - Noriah Hamit; Khalib Abd Latip (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional study was conducted to identify the practices for controling the breeding of Aedes mosquitoes amongs the residents of Kampung Padang Jawa Petaling Selangor. A study involved a total of 200 respondents from 200 houses that were chosen randomly. Respondents were interviewed and their houses were checked for Aedes breeding places. Results showed 21% of the responden had Aedes breeding places at their houses. The majority of the respondents (83%) had poor knowledge regarding treatment of dengue. The majority of the respondents (82%) did not know that Abate can be used in the dril1king water. There were misconceptions amongs 77% of the respondents that Aedes mosquitoes lay eggs in filthy and dirty municipal drains Almost half of the respondents did not know the various law regarding the control dengue. The levels of general knowledge on dengue were significantly correlate (p<0.05) with attitude towards dengue control. Practices of breeding Aedes mosquitoe: were found to be significantly related with working status and knowledge on dengue In conclusion, there is a need to increase the levels of knowledge about Aedes breeding for better dengue control in future.